Pengelolaan Terbitan Berseri di Perpustakaan Universitas Andalas (Unand) - Utami, Juni Putri; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this study was to describe the procurement, processing and forms of serial publications service, as well as the obstacles that cause has not been optimal management of serial publications in the Library of Unand. This research is a qualitative and use descriptive method. The data obtained by direct observation, interview and literature. The study's findings are management of serial publications in Library of Unand not optimal. This is caused by several things, namely: the procurement serial publications is generally sourced from the prize, processing serial publications that has not been good and the search tool is not available, the form of serial publications service a limited, and the problems encountered by the Library of Unand in managing the serial publications includes: (1) insufficient funds and the management of centralized budgeting, (2) the librarian of serial publications is not library educational background, (3) lack of facilities such as a computer that can support the management of serial publications, (4) the head of the library is less motivating his subordinates, (5 ) promotion of serial publications is made less, (6) not timely arrival of publications serial makes that collection be administered up to date for all library users.